Z Object. Zukofsky in Argentine Poetry (Anclajes, 2025)
The journey of North American poet Louis Zukofsky in contemporary Argentine poetry is very brief but significant. In this article, I first examine Zukofsky's initial appearances. The first time his name is mentioned is in Martín Gambarotta’s “Ars Poetica”, as part of Arturo Carrera’s anthology Monstruos (2001). The second is in 2010, when Sergio Raimondi composed a Hypermedia Box for the Bazar Americano site based on a poem by William Carlos Williams, whose words are hyperlinks to essays and poems by Zukofsky, translated by Raimondi himself. Then, I turn to Tomás Fadel’s translation of section 12 of Zukofsky's book A, published in 2015. The article argues that these three instances of articulation of “object Z” in turn allow us to distinguish and define different modulations of objectivism.
Keywords: Louis Zukofsky; Poetry; Translation; 21st century; Argentina